МАКТАБГАЧА ЁШДАГИ БОЛАЛАР БИЛАН АЛОҚА ЎРНАТИШДА УЛАР КОММУНИКАТИВ ҚОБИЛИЯТЛАРИНИНГ ПСИХОЛОГИК ХУСУСИЯТЛАРИНИ АНИҚЛАШ - Дж.Бекова, Ш. (SCIENCE and SOCIETY, 2020)
This article discusses the role of psychological characteristics in the development of communicative skills, protecting preschool children from difficulties in teaching communicative abilities.
Keywords: educational establishment; preschool child; foster; communicative skill; psychological character; attitude; child; parents; positive attitude; development; communicative rapport; opportunity